2022
DOI: 10.3389/fphys.2022.880891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbid Prematurity and Congenital Anomalies: A Review

Abstract: Preterm infants are more likely to be born with congenital anomalies than those who are born at full-term. Conversely, neonates born with congenital anomalies are also more likely to be born preterm than those without congenital anomalies. Moreover, the comorbid impact of prematurity and congenital anomalies is more than cumulative. Multiple common factors increase the risk of brain injury and neurodevelopmental impairment in both preterm babies and those born with congenital anomalies. These include prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
(68 reference statements)
1
4
0
1
Order By: Relevance
“…We found that the most common comorbidities were perinatal diseases (87.50%) in children with CHD, and 47.55% of children with perinatal diseases also reported CHD. A study showed that newborns with CHD were more likely to be born prematurely and/or small for gestational age than those without CHD [ 17 ], which was consistent with our findings. According to clinical experience, the symptoms of CHD patients are shortness of breath, heart murmur, low body weight, and repeated respiratory tract infections [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the most common comorbidities were perinatal diseases (87.50%) in children with CHD, and 47.55% of children with perinatal diseases also reported CHD. A study showed that newborns with CHD were more likely to be born prematurely and/or small for gestational age than those without CHD [ 17 ], which was consistent with our findings. According to clinical experience, the symptoms of CHD patients are shortness of breath, heart murmur, low body weight, and repeated respiratory tract infections [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…[24][25][26] Other studies have also remarked that a prolonged hospital stay may be related to suboptimal longterm morbidity and neurodevelopment outcomes. 27,28 Postoperative complications such as gastroesophageal reflux disease with need for antireflux surgery and anastomotic strictures were similar among analyzed centers. Although not statistically significant, there were observed differences in the rate of anastomotic leakage (15% for center A and 0% for center B), which may result from the utilization of routine postoperative contrast study; importantly, there were no leaks that required surgical management.…”
Section: Discussionmentioning
confidence: 72%
“…A long initial hospital stay, as well as significant associated anomalies, and persistent digestive or respiratory symptoms may negatively influence on health related quality of life (HRQOL) [24]. Other studies have also remarked that a prolonged hospital stay may be related to suboptimal long-term morbidity and neurodevelopment outcomes [25,26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…З одного боку, існує значна кількість антенатальних факторів ризику, що можуть як безпосередньо спричиняти неонатальне ураження головного мозку, так і виступати в ролі тригерів у неонатальному періоді. З іншого боку, передчасно народжені діти є найбільш уразливою категорією пацієнтів загалом і навіть за найбільш сприятливого перебігу неонатального періоду потребують додаткової респіраторної підтримки, значної кількості інвазивних медичних втручань і мають великий ризик інфекційних ускладнень [7,11]. За даними останніх досліджень, частота раннього неонатального сепсису сягає близько 11 випадків на 1000 немовлят, народжених із масою <1500 г. Рівень захворюваності на пізній неонатальний сепсис становить 51,2% у немовлят з ЕММТ, 15-25% у немовлят із ДММТ і 1,6% у немовлят із масою ≥2500 г [3,10].…”
Section: оригінальні дослідженняunclassified